2015
DOI: 10.1111/1742-6723.12432
|View full text |Cite
|
Sign up to set email alerts
|

Tyranny of distance and rural prehospital care: Is there potential for a national rural responder network?

Abstract: Critical illness intersects with the workload of rural doctors in Australia, mostly via their on-call responsibilities to rural hospitals. A significant proportion of these are prehospital incidents - vehicle crashes, farming injuries, bushfire etc. Effective care for such patients requires an integration of prehospital ambulance services, retrieval services and tertiary level trauma services all the way through to rehabilitation. Ambulance services in rural areas are often volunteer based, and with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…For example, health service bodies regulating rural doctors may have conducted more recent studies for the purposes of quality improvement but limited their publication to organisational reports. Furthermore, some research has been published as perspectives, such as a 2015 paper published in Emergency Medicine Australasia which included a survey on emergency medicine course attendance and preparedness of rural doctors …”
Section: Discussionmentioning
confidence: 99%
“…For example, health service bodies regulating rural doctors may have conducted more recent studies for the purposes of quality improvement but limited their publication to organisational reports. Furthermore, some research has been published as perspectives, such as a 2015 paper published in Emergency Medicine Australasia which included a survey on emergency medicine course attendance and preparedness of rural doctors …”
Section: Discussionmentioning
confidence: 99%
“…Mackay with a population of 76,069 falls into this category. We can therefore state that the services in the major cities in Australia are more reliable than the regional areas (see Hamilton et al, 2010 andLeeuwenburg andHall, 2015).…”
Section: Ambulance Locations In Rural and Urban Areasmentioning
confidence: 98%
“…Studies have shown that GPs in Ireland, Canada and Australia encounter a variety of emergencies and perform a wide range of interventions [5,6,7]. In another study from Ireland, 36% of GP practices were involved in a cardiac arrest during a 5-year period.…”
Section: Introductionmentioning
confidence: 99%